1979
DOI: 10.1007/bf01317491
|View full text |Cite
|
Sign up to set email alerts
|

Effect of trisodium phosphonoformate in genital infection of female guinea pigs with herpes simplex virus type 2

Abstract: A genital herpesvirus type 2 infection in guinea pigs has been used to evaluate the inhibitory effect of phosphonoformate on the infection. An early topical treatment prevented the appearance of vesicles and histopathological changes and no virus could be recovered. When treatment, either topical or both systemic and topical, was delayed to 24 hours post infection no therapeutic effect was observed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
6
1

Year Published

1980
1980
1986
1986

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(7 citation statements)
references
References 25 publications
0
6
1
Order By: Relevance
“…Viral shedding and HSV-induced vaginal cytology abnormali ties were significantly lessened in drug-treated animals as compared to sham-treated animals, although virus could readily be detected in the nervous system of animals from either group. This result differs from an earlier report of a guinea pig model of HSV2 infection in which combined systemic and topical treatment was ineffective if begun later than 24 h after infec tion, although topical treatment alone was effective if begun within 4 h of infection [7]. In the present study not only were higher doses of PFA used than were used previously (86 mg/ day vs. 75 mg/day), but treatment was con tinued for an additional day (5 days vs. 4 days).…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…Viral shedding and HSV-induced vaginal cytology abnormali ties were significantly lessened in drug-treated animals as compared to sham-treated animals, although virus could readily be detected in the nervous system of animals from either group. This result differs from an earlier report of a guinea pig model of HSV2 infection in which combined systemic and topical treatment was ineffective if begun later than 24 h after infec tion, although topical treatment alone was effective if begun within 4 h of infection [7]. In the present study not only were higher doses of PFA used than were used previously (86 mg/ day vs. 75 mg/day), but treatment was con tinued for an additional day (5 days vs. 4 days).…”
Section: Discussioncontrasting
confidence: 56%
“…In a guinea pig model of genital in fection with HSV2, it was reported that topical PFA treatment begun within 24 h after inocu lation decreased disease severity and viral shedding. Combined topical and systemic treatment begun after this time had no thera peutic effect [7]. Because infected patients are not likely to seek medical advice until after the disease is apparent, we investigated the effects of PFA on genital HSV2 infections after the appearance of symptoms.…”
mentioning
confidence: 99%
“…Effective ACV and phosphonoformic acid (PFA) treatment of genital herpes in guinea pigs is well documented (1,4,6,10 laboratory (6, 10, 22) and is comparable to those used in other studies (8,14).…”
mentioning
confidence: 52%
“…Effective ACV and phosphonoformic acid (PFA) treatment of genital herpes in guinea pigs is well documented (1,4,6,10). This model has also been used to show the potential of prophylactic therapy with a lipid amine (22), minimal effect of treatment with adenine arabinoside and several of its analogs (12), and failure of treatment with 2-deoxy-D-glucose (5,15 to inhibition by bromovinyldeoxyuridine (9), by its inability to induce an HSV-1-specific enzyme (21), and by neutralization with HSV-2-specific antisera.…”
mentioning
confidence: 99%
“…Candidate antiviral drugs that have proven to be effective against HSV-2 infections in animal models and that therefore seem worth pursuing for their potential in the treatment of genital herpes and HSV-2 infections in general include cyclaradine (43) as well as its predecessor vidarabine (34); the 1-(2'-deoxy-2'-fluoro-p-D-arabinofuranosyl)pyrimidine derivatives FMAU, FIAC, and FIAU (27,28); 5-ethyl-2'-deoxyuridine (EDU) (39); phosphonoformate (1,23,24,28); and 9-(1,3-dihydroxy-2-propoxymethyl)guanine (21), particularly when combined with interferon (18)(19)(20). Cyclaradine, vidarabine, and phosphonoformate thereby offer the advan-* Corresponding author.…”
mentioning
confidence: 99%